1970
DOI: 10.1002/jez.1401750404
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian lung development: Interactions in primordium formation and bronchial morphogenesis

Abstract: The manner in which mouse lung primordia form has been analyzed by observation of trypsin-isolated gut endoderm from nine-day embryos. The tissue interactions involved in initial formation of lung primordia and those involved in subsequent morphogenesis of the primordia have been investigated by various organ culture procedures. Mouse lungs form in a manner different from that generally described for amniote embryos. Thus, two lung buds appear first and form the primary bronchi, whereas the trachea appears sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
2

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(94 citation statements)
references
References 9 publications
1
91
0
2
Order By: Relevance
“…In embryonic lung explants, bronchial mesoderm is required for branching of the lung buds, demonstrating the importance of epithelial/mesenchymal interaction in lung development (Alescio and Cassini, 1962;Spooner and Wessels, 1970;Alescio and Dani, 1971). Our present findings suggest that FGFs are likely mediators of this crucial interaction.…”
Section: Resultsmentioning
confidence: 99%
“…In embryonic lung explants, bronchial mesoderm is required for branching of the lung buds, demonstrating the importance of epithelial/mesenchymal interaction in lung development (Alescio and Cassini, 1962;Spooner and Wessels, 1970;Alescio and Dani, 1971). Our present findings suggest that FGFs are likely mediators of this crucial interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Growth and differentiation of the lung endoderm is strictly dependent on signaling from the mesenchyme. Classical recombination experiments mixing lung endoderm with distal versus proximal lung mesenchyme showed that the mesenchyme provides instructional cues for endodermal morphogenesis and cell lineage determination (14). It is important to note that the mesenchyme is also a source of cells contributing to a number of functional compartments in the lung including the vasculature and the airway smooth muscle.…”
Section: Rmentioning
confidence: 99%
“…This dual origin of lung tissues is critical in development. Removal of mesenchyme from the tip of a lung bud during early phases of development with transplantation to the side of a higher ordered segment abolishes further branching at the site of removal while stimulating growth of a new branch at the site of transplantation (14). Lung (4).…”
Section: Embryogenesismentioning
confidence: 99%